If it's not what You are looking for type in the equation solver your own equation and let us solve it.
62=d/5+7
We move all terms to the left:
62-(d/5+7)=0
We get rid of parentheses
-d/5-7+62=0
We multiply all the terms by the denominator
-d-7*5+62*5=0
We add all the numbers together, and all the variables
-1d+275=0
We move all terms containing d to the left, all other terms to the right
-d=-275
d=-275/-1
d=+275
| X+1*4x+10=90 | | x=x/33,8 | | -11+8n+6-4=n+5 | | (x-6)÷4-(x-4)÷6=1-x÷12 | | 16x+42=132 | | -8(4p+1=-37-3p | | (4x-3)^2+(4x+3)^2=26 | | -8p+3=3-8p | | 5(x-5)+4=-6 | | 3•(x+1)=2x+5 | | 5^x-5^-x÷2=3 | | 5w+3=4w=9 | | 4x^2+4x=-55 | | 8(4p+1)=-37-3p | | 5x-6=19-(5x+6) | | 6+-3z=9 | | 4b-30=-(b-5) | | 12w+32=100 | | 2(w-(2w+14)+10)=2(w+4) | | 4-2c=18 | | -24+8x=-6(5x+4) | | (36÷(24-x)+29)÷5=7 | | 4h+8=-5 | | j-1+1=0 | | 3x18=2x+10 | | 4x+7x=10+16 | | 6=2(y=2) | | 2n+36=-4(1-3n) | | 18x-4=10x | | 24x=12x+48 | | -2p-3(6-3p)=3(p-6)-28 | | q3– 1= 1 |